Experimental determination of plagioclase dissolution rates as a function of its composition and pH at 22°C - Gudbrandsson, S.; Wolff-Boenisch, Domenik; Gislason, S.; Oelkers, E. (Pergamon, 2014)
The steady-state, far-from-equilibrium dissolution rates of nine distinct plagioclases ranging in composition from An2 to An89 were measured in mixed flow reactors at 22 ± 2 °C and pH from 2 to 11. The dissolution rates of all plagioclases based on silica release show a common U-shaped behaviour as a function of pH, where rates decrease with increasing pH at acid condition but rise with increasing pH at alkaline conditions. Consistent with literature findings, constant pH plagioclase dissolution rates increase with increasing anorthite content at acidic conditions; measured anorthite dissolution rates are ∼2.5 orders of magnitude faster than those of albite at pH ∼2. Perhaps more significantly, rates are independent of plagioclase composition at alkaline conditions. Interpretation and data fitting suggests that plagioclase dissolution rates are consistent with their control by the detachment of Si-rich activated complexes formed by the removal of Al from the mineral framework. Taking account of this mechanism and transition state theory yields equations describing plagioclase dissolution rates (r+) as a function of both the mineral and aqueous fluid compositions found in natural Earth surface systems. For pH ⩾ 6 rates are consistent with View the MathML sourceLog(r+/(mol/cm2/s))=0.35Log(aH+3/aAl3+)-11.53 and for pH < 6 rates are consistent with View the MathML sourceLog(r+/(mol/cm2/s))=nacidLog(aH+3/aAl3+)+0.033An%-14.77 where An% represents the percent anorthite in the plagioclase solid solution, ai corresponds to the activity of the ith aqueous species, and nacid is given by nacid=0.004An%+0.05nacid=0.004An%+0.05.